Brain Delivery of Cisplatin Using Microbubbles in Combination with Ultrasound as an Effective Therapy for Glioblastoma - Fumiko Hagiwara; Daiki Omata; Lisa Munakata; Saori Kageyama; Kazuo Maruyama; Nobuki Kudo; Ryo Suzuki (MDPI AG, 2023)
Glioblastoma is a highly invasive and fatal disease. Temozolomide, a blood-brain barrier (BBB)-penetrant therapeutic agent currently used for glioblastoma, does not exhibit sufficient therapeutic effect. Cisplatin (CDDP), a versatile anticancer drug, is not considered a therapeutic option for glioblastoma due to its low BBB permeability. We previously investigated the utility of microbubbles (MBs) in combination with ultrasound (US) in promoting BBB permeability and reported the efficacy of drug delivery to the brain using a minimally invasive approach. This study aimed to evaluate the feasibility of CDDP delivery to the brain using the combination of MBs and US for the treatment of glioblastoma. We used mice that were implanted with glioma-261 GFP-Luc cells expressing luciferase as the glioblastoma model. In this model, after tumor inoculation, the BBB opening was induced using MBs and US, and CDDP was simultaneously administered. We found that the CDDP concentrations were higher at the glioblastoma site where the US was applied, although CDDP normally cannot pass through the BBB. Furthermore, the survival was longer in mice treated with CDDP delivered via MBs and US than in those treated with CDDP alone or those that were left untreated. These results suggest that the combination of MBs and US is an effective antitumor drug delivery system based on BBB opening in glioblastoma therapy.